Inpatient satisfaction survey with the communication and behavior of medical staffs in 7A Military Hospital, Ho Chi Minh City, Vietnam - Giang Tran, Thi Huong; Le, Quang-Tri (International Journal Of Community Medicine And Public Health, 2020)
Background: This study was done to determine the degree of inpatients’ satisfaction in the 7A Military Hospital (Ho Chi Minh City, Vietnam). Methods: A cross-sectional research has been designed to survey the satisfaction of 138 inpatients before discharge for 36 communication and behavior aspects of the hospital’s medical staff. Results: The average satisfaction score was very high (mean=4.27; SD=0.49). However, the percentage of unsatisfied inpatients was still quite high (8.3%). Conclusions: Very satisfied percentage 37.6%; satisfied 54.1%, somewhat satisfied 6.7%, not satisfied 1.2% and very unsatisfied 0.4%. It has been concluded that the nursing code of conduct issued by the Ministry of Health was relatively match with patient’s expectation and lead to high patients’ expectation when implemented closely. However, the hospital itself needed further improvement in administration and management to improve satisfaction further.